The private premium in public bonds - Anna Kovner; Chenyang Wei (Federal Reserve Bank of New York, 2012)
This paper is the first to document the presence of a private premium in public bonds. We find that spreads are 31 basis points higher for public bonds of private companies than for bonds of public companies, even after controlling for observable differences, including rating, financial performance, industry, bond characteristics and issuance timing. The estimated private premium increases to 40-50 basis points when a propensity matching methodology is used or when we control for fixed issuer effects. Despite the premium pricing, bonds of private companies are no more likely to default or be downgraded than are public bonds. They do not have worse secondary market performance or higher credit default swap spreads nor are they necessarily less liquid. Bond investors appear to discount the value of privately held equity. The effect does not come only from the lack of a public market signal of asset quality, because very small public companies also pay high spreads.
Keywords: G12; G14; G32; 330; bonds; private; private equity